Improving Students' Pronunciation Through the "Say It" Application at SMA Negeri 8 Makassar: SMA Negeri 8 Makassar - Revananda, Adriana; Nunung Anugrawati, Nunung Anugrawati; Ariana, Ariana (Journal of Computer Interaction in Education, 2025)
The purpose of this research was to figure out how to assist youngsters pronounce words properly using the "Say It" app at SMA Negeri 8 Makassar. A pre-experimental design and quantitative research approach were employed in this investigation. To collect study data, pre-test, treatment, and post-test techniques were employed. The proper pronunciation of twenty words from the pre- and post-tests is required. According to study results, utilizing the "Say It" app enhanced students' pronunciation dramatically. Prior to therapy, the average score was 70.3, and after treatment, the average score was 90.3, suggesting a 28.44% increase in percentage. This suggests that the kids' pronunciation has improved.